2021
DOI: 10.1111/eci.13638
|View full text |Cite
|
Sign up to set email alerts
|

Clinical conditions and echocardiographic parameters associated with mortality in COVID‐19

Abstract: Background Coronavirus disease 2019 (COVID‐19) is a recently recognized viral infective disease which can be complicated by acute respiratory stress syndrome (ARDS) and cardiovascular complications including severe arrhythmias, acute coronary syndromes, myocarditis and pulmonary embolism. The aim of the present study was to identify the clinical conditions and echocardiographic parameters associated with in‐hospital mortality in COVID‐19. Methods This is a multicentre r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 49 publications
2
36
0
1
Order By: Relevance
“…In a previous study by our register, we have demonstrated that PE was a relatively common complication in hospitalized patients with COVID-19 and was associated with a poorer outcome [31]. Although associated with in-hospital mortality [32], in the present analysis, LVEF did not correlate with PE after adjustment for PAPS and TASE/PASP values, supporting the importance of these measures for PE risk stratification in this population.…”
Section: Discussionsupporting
confidence: 59%
“…In a previous study by our register, we have demonstrated that PE was a relatively common complication in hospitalized patients with COVID-19 and was associated with a poorer outcome [31]. Although associated with in-hospital mortality [32], in the present analysis, LVEF did not correlate with PE after adjustment for PAPS and TASE/PASP values, supporting the importance of these measures for PE risk stratification in this population.…”
Section: Discussionsupporting
confidence: 59%
“…We used 23 articles in this section. Cardiac injury was a crucial and independent risk factor for mortality in COVID-19-infected patients [12,[21][22][23] and mortality was usually higher in the cardiac injury group [7,9,[23][24][25]. Patients with cardiac injury were older [7,11,22,26], had more comorbidities [22,25,26], were mostly male [10,22], had more serious disease [7,22,23] or were more likely to require mechanical ventilation [21,22].…”
Section: Hospitalisation and Outcomementioning
confidence: 99%
“…Since these first observations it is become clear that the same cytokines that induce aberrant endothelial function may also trigger the acute phase response, which, in combination with local endothelial dysfunction, can lead to clinical consequences ( 14 ); indeed, inflammatory cytokines have a major role in both diabetes and cardiovascular diseases ( 19 ). Other authors have shown that COVID-19 is associated with myocardial damage such as myocarditis, arrhythmia and reduced left ventricular ejection fraction ( 20 ), all of which are associated to increased mortality risk ( 21 ). Plasma cardiac biomarkers, such as high sensitivity troponin, creatine kinase and N-terminal pro-B-type natriuretic peptide, are also associated with COVID-19 severity in adults and children ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%